1997
DOI: 10.1007/bf02055689
|View full text |Cite
|
Sign up to set email alerts
|

Is colonic electrical activity a similar phenomena to small-bowel electrical activity?

Abstract: PURPOSE: This study was designed to investigate colonic spike bursts regarding 1) their migration behavior, 2) their pressure correlates, and 3) comparing colonic short spike bursts with spike bursts from migrating myoelectric complex from the small bowel. METHODS: Rectosigmoid electromyography and manometry were recorded simultaneously in seven normal volunteers and electromyography alone in five others during two hours of fasting and for two hours after one 2,100-kJ meal. One patient with an ileostomy was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…44,45 In human studies, acute aerobic exercise decreased colonic phasic motor activity, resulting in less resistance to colonic flow, while postexercise increased the number and amplitude of propagated waves, which was thought to induce propulsion of stool. 46 Kim et al found that an exercise as simple as walking improved colonoscopy preparation among younger, nonobese patients with no history of abdominal surgery.…”
Section: Effect Of Exercise On Gastrointestinal Motilitymentioning
confidence: 99%
“…44,45 In human studies, acute aerobic exercise decreased colonic phasic motor activity, resulting in less resistance to colonic flow, while postexercise increased the number and amplitude of propagated waves, which was thought to induce propulsion of stool. 46 Kim et al found that an exercise as simple as walking improved colonoscopy preparation among younger, nonobese patients with no history of abdominal surgery.…”
Section: Effect Of Exercise On Gastrointestinal Motilitymentioning
confidence: 99%
“…The mechanism of rectal motility is not yet fully elucidated (Schafer et al, 1996;Cortesini et al, 1995). Electric activity could be recorded from different parts of the gut including the stomach (Kauer et al, 1999;Levanon & Chen, 1998), small (Aube et al, 1999;Medeiros et al, 1997) and large gut (Abo et al, 2000;Julia et al, 1999) and liver (Shafik, 2000). It occurs in the form of slow waves or pacesetter potentials (PPs) and fast activity spikes or action potentials (APs).…”
Section: Introductionmentioning
confidence: 98%
“… 4 This increased colonic motor activity results in increased migrating and nonmigrating long spike bursts. 5 …”
Section: Introductionmentioning
confidence: 99%
“…4 This increased colonic motor activity results in increased migrating and nonmigrating long spike bursts. 5 In recent years, high-resolution colonic manometry has provided greater insight into stationary and propagating colonic motor patterns. [6][7][8] In particular, the colonic response to feeding has shown that the sigmoid colon is the most impacted digestive segment during the phasic motor response of digestion, which consists of peristaltic waves that propel feces distally toward the rectum.…”
Section: Introductionmentioning
confidence: 99%